The Growth on the Maximum Modulus of Double Dirichlet Series. (10th January 2019) - Cui, Yong-Qin; Xu, Hong-Yan; Li, Na
Abstract : The main purpose of this paper is to investigate the growth of several entire functions represented by double Dirichlet series of finite logarithmic order, h -order. Besides, we also study some properties on the maximum modulus of double Dirichlet series and its partial derivative. Our results are extension and improvement of previous results given by Huo and Liang.